A New World Order for the Beer Industry: A Review of the Acquisition of SABMiller by Anheuser‐Busch AB InBev1. (9th May 2019) - Bamber, Matthew
ABSTRACT: This case study reviews one of the largest merger and acquisition transactions in corporate history—the acquisition of SABMiller by Anheuser‐Busch InBev. This study provides information to value the post‐transaction combined entity and provide an investment recommendation. Following this, the case discusses the basic details of the funding required to undertake the acquisition and questions which implications of any additional financial risk may arise for AB InBev from a valuation perspective. Abstract : Un nouvel ordre mondial pour l'industrie de la bière : Analyse de l'acquisition de SABMiller par Anheuser‐Busch InBev: Résumé: L'étude de cas proposée par l'auteur porte sur l'analyse de l'une des plus importantes opérations de fusion‐acquisition de l'histoire : l'acquisition de SABMiller par Anheuser‐Busch InBev. Dans les renseignements fournis figurent les données permettant d'évaluer l'entité issue du regroupement ainsi qu'une recommandation d'investissement. Sont ensuite analysés les éléments essentiels détaillés du financement qu'exige l'acquisition et les questions que pourraient soulever les conséquences de tout risque financier supplémentaire pour AB InBev, du point de vue de l'évaluation.